Shrinking the US leadership role: populism and the change of domestic and international “others” - Friedrichs, Gordon; Harnisch, Sebastian (National role conceptions in a new millennium, 2022)
The US leadership role has been crucial for the establishment and maintenance of the post-World War II order. A shared national role conception of functional scope and external “Others” substantiated America's global public goods provision for the past decades. In this chapter, we trace the rise of populism in US politics in the form of Donald Trump and the subsequent relative delimitation of America's global engagement. We begin by distinguishing between four different versions of international leadership roles that are contingent on an agenda-setter and representative auxiliary role. We then employ a quantitative content analysis to track shifts in the national role conceptions of the president regarding US global leadership. In a final step, we trace these populist role conceptions of US leadership in two policy fields: alliance politics and trade. Our findings indicate that Trumpian populism translates into a functional role based on transactions and nationalism that rewards power and disregards weakness. This chapter sheds light on the scope and drivers of shifts in US leadership under the Trump presidency as well as offers a methodological approach to the study of national role conceptions.
Gesehen am 03.05.2023